Geophagia : history, epidemiology, and etiology - Gupta, Anil (Child nutrition scientist) (Boca Raton : CRC Press, 2020)
"The consumption of soil, clay and chalk by humans is labeled as geophagia. This book takes a consistent, interdisciplinary approach for reviewing this aberrant behavior, crafting its etiology, charting its health effects and identifying the universal traits among the affected population"--
Introduction of geophagia -- History of geophagia -- Epidemiology of geophagia -- Etiology of geophagia -- Effects of geophagia on nutritional status of preschool children.
OCLC-licensed vendor bibliographic record.
Keywords: Pica (Pathology) -- History; MEDICAL / Family & General Practice; MEDICAL / Pediatrics; MEDICAL / Public Health